2009
DOI: 10.1159/000235250
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cell-Free DNA Levels in Children on Peritoneal Dialysis

Abstract: Background/Aims: Plasma levels of cell-free DNA (cfDNA) are elevated in various clinical conditions including cancer, stroke, trauma, myocardial infarction, autoimmune disorders, and pregnancy-associated complications. Previously, increased cfDNA levels were reported during hemodialysis. However, there is limited data regarding cfDNA levels in peritoneal dialysis (PD) patients. The aim of this study was to investigate the levels of cfDNA in children on PD. Methods: Twenty-one children on PD (median age: 12; ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…However there is still a long way to go for widespread routine clinical application. [2,[4][5][6][7][8][9][10] The exact mechanism of cfDNA presence in circulation is not clear. Release from apoptotic or necrotic cells are reported to be among the main sources [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However there is still a long way to go for widespread routine clinical application. [2,[4][5][6][7][8][9][10] The exact mechanism of cfDNA presence in circulation is not clear. Release from apoptotic or necrotic cells are reported to be among the main sources [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The origin is reported to be the apoptosis of lymphocytes and other nucleated cells or an active physiological secretion by lymphocytes [1][2][3] Elevated levels of cell-free nucleic acids have been reported in various clinical conditions such as cancer, stroke, trauma, myocardial infarction, autoimmune disorders, pregnancy complications and peritoneal dialysis. This fact has stimulated researchers to investigate the possibility to use circulating nucleic acids as a potential marker for early detection or follow-up of some diseases [2,[4][5][6][7][8][9][10]. Henoch-Schönlein purpura (HSP) is the most common vasculitic disease of childhood with potentially serious systemic involvement.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s (after the landmark papers by Chen et al [12] and Nawroz et al [13] were published) this observation initiated a surge of papers confirming and extending the results described by Leon et al Unfortunately, it became clear very soon that the increase in cfDNA in tumor patients is not specific and that many factors/diseases lead to the higher quantity of cfDNA (see chapter "The Biology of CNAPS"). When cfDNA had been quantified it was shown that the amount is increased in a variety of different conditions such as myocardial infarction [14], cardiac arrest [15], exhaustive exercise [16][17][18], in patients with systemic lupus erythematosis [19], in older humans [20], in febrile patients [21], in children on peritoneal dialysis [22], in patients with obstructive sleep apnea [23], patients with chronic kidney disease [24], patients with severe sepsis or septic shock [25], in trauma [26] and burn patients [27] (chapter "CNAPS and General Medicine"). In an attempt to differentiate lung cancer patients from a control population according to their sputum cfDNA it was demonstrated that the amount of cfDNA was related to the severity of the inflammatory processes but not the presence of lung cancer [28].…”
Section: Dna Quantification/dna Integritymentioning
confidence: 99%
“…However, the signal contamination from single-stranded nucleic acids, proteins and RNA contributes to the poor specificity and decreased sensitivity for the quantitative analysis of low concentration CCFDNA. The development of DNA specific reagents such as Invitrogen’s PicoGreen ® dsDNA quantitation reagent assays [90], real-time quantitative PCR assay (RT-qPCR) [9, 55, 9197], digital PCR approach [98], and fluorometric PCR assay [99, 100] have decreased the sample size requirement and increased the reliability of CCFDNA identification and quantitation.…”
Section: Quantification Of Circulating Cell Free Dnamentioning
confidence: 99%